Bacterial microbiota composition of a common ectoparasite of cavity‐breeding birds, the Hen Flea Ceratophyllus gallinae. (14th January 2020) - Aivelo, Tuomas; Tschirren, Barbara
Abstract : Experimental field studies have demonstrated negative fitness consequences of Hen Flea Ceratophyllus gallinae infestations for bird hosts, yet it is currently unclear whether these negative effects are a direct consequence of flea‐induced blood loss or a result of flea‐borne pathogen transmission. Here we used a 16S rRNA gene sequencing approach to characterize the bacterial microbiota community of Hen Fleas collected from Great Tit Parus major nests and found that Brevibacterium (Actinobacteria), Staphylococcus (Firmicutes), Stenotrophomonas (Proteobacteria), Massilia (Proteobacteria), as well as the arthropod endosymbionts ' Candidatus Lariskella' and ' Candidatus Midichloria' were most abundant. We found evidence for the occurrence of Staphylococcus spp. in Hen Fleas, which may cause opportunistic infections in bird hosts, but not of other known pathogens commonly transmitted by other flea species, such as Bartonella spp. or Rickettsia spp. However, Hen Fleas might transmit other pathogens (e.g. viruses or bacteria that are not currently recognized as bird pathogens), which may contribute to the negative fitness consequences of Hen Flea infestations in addition to direct blood loss or secondary infections of wounds caused by biting fleas.